Sustainable Behaviors of Young Polish Consumers: the Impact on Logistics and Business Strategies - Hanus, Gabriela (European Journal of Sustainable Development, 2024)
The main objective of this survey is to analyze the sustainable behavior of young Polish consumers. The specific objectives are to find out the respondents' opinions on the most disturbing environmental phenomena and actions that negatively affect the environment. In addition, an important goal is to learn about their self-assessment of pro-environmental attitudes and to identify pro-environmental actions most often taken by young consumers, as well as to assess sustainable actions taken by companies in the logistics area. The results are based on empirical research concerning sustainable behaviors of young Polish consumers in a research sample of 50 consumers. The research was conducted in April and May 2024 and covered the entire area of Poland. The survey show that respondents have a good assessment of their environmental attitude. As many as 90% of them perceive growing environmental and social problems. The most worrisome environmental issues in their view are increased garbage and waste, polluted air and water, dangerous chemicals in everyday products, and climate change-the greenhouse effect. Among the activities that have the most detrimental impact on the environment, respondents identified deforestation, improper waste management, consumerism, pollution from pesticides used in agriculture and the burning of fossil fuels. Three-quarters of respondents believe they can contribute to improving the environment with their actions, and nearly two-fifths say they are willing to pay more for environmentally friendly products or products from companies that support social causes. Respondents also take a number of individual pro-environmental measures, and among them they are most likely to turn off lights, use reusable bags, segregate trash, use reusable bottles, conserve water and choose environmentally friendly forms of delivery for purchased goods. However, when making purchases, most of them do not choose products offered by companies that are actively involved in environmental activities. Up-to-date knowledge on the sustainable behavior of young consumers is particularly important for both the business and government communities, as it provides information on tailored strategies and policies that align with evolving values, ensuring competitiveness, and meeting environmental and social goals. Limitations of the study include the small sample size of the empirical study, as well as the limited nature of the survey questionnaire. Keywords: sustainability, social responsibility, sustainable consumer, young generation consumer